Equipamentos urbanos de infraestrutura e criminalidade: uma abordagem para os municípios mineiros - Daniel do Nascimento Silva (2012)
This work approaches the hypothesis about the association between creation and maintenance of urban equipment of infrastructure and criminality reduction. Several theoretical models legitimize this negative relationship by giving importance to the environment as an important factor in explaining the crime. From an economic standpoint, the initiatives on public space reduce favorable opportunities to the execution of a crime and increase the level of social interaction in a community which can be considered as criminality reduction factors. The present work, based on military police information about crime rates in Minas Geraiss cities, pretends to contribute to this debate by presenting empirical evidences on this association. We use an spatial econometric model based on the method of general spatial two stages least squares to incorporate the possible spillover effects of the criminality phenomenon. The estimation is performed considering as dependent variable the crime rate growth of the years 2001 to 2007 when police reports are more reliable. Crime is tackled by disaggregating the range of crimes as follow: crimes against property, crimes against persons and homicides taking the period between 2001 and 2007. Urban equipment of infrastructure are represented by an index of infrastructures basic equipments, constructed from principal components analysis, in addition to per capita spending on housing and urbanization and proportion of people living in households which are not subnormal. The results show that cities which exhibit a high index of infrastructures basic equipments have lower growth rates of the three types of crime between 2001 and 2007. The per capita expenditure on housing and urbanism negatively impacts on the growth rate of crime against property and the growth rate of homicides between 2001 and 2007. These results corroborate the theoretical assumptions that negatively associate the creation and maintenance of infrastructures urban equipments and the manifestation of violent criminality.